Uji Getaran Rangka Tabung Sentrifugal Mesin Produksi Santan Kapasitas 10 Liter Per Jam - Herdi Susanto; Syurkarni Ali; Sulaiman Ali; M Khalil (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2021)
Abstract Coconut plantations reach more than 106 hectares of the 831 thousand hectares of plantation areas in Aceh. Meanwhile, the total production reached 63 thousand tons with a productivity level of 818 kilograms per hectare. Most of it is still traditionally produced to produce coconut milk from these coconuts. The design of the coconut milk production machine has been carried out and before it is used a vibration test must be carried out to determine the operational feasibility of the machine. This study aims to measure the vibration level of the centrifugal tube frame for the coconut milk production machine with a centrifugal system capacity of 10 L / hour. The test was carried out at three levels of motor rotation, namely 1000 rpm, 1500 rpm and 2000 rpm with repeated measurements carried out five times at each motor rotation speed, the measurement results were compared with ISO 2631-1 standards and Kepmenaker number KEP-51 / MEN / I999. The results showed that testing the vibration of a coconut milk production machine with a centrifugal system with a capacity of 10 L / hour stated that it was safe if it was operated for less than 4 hours for a motor rotating speed of 1000 rpm, for a motor rotating speed of 1500 rpm it was safe to use if it was operated for less than 3 hours, while for rotation 2000 rpm motor is good and comfortable to use for less than 2 hours. Keywords— centrifugal tube, coconut squeezer, SO 2631-1, KEP–51/MEN/I999